2022
DOI: 10.1007/s40519-022-01386-7
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric comorbidities and dehydration are more common in children admitted to the emergency department for eating disorders in the COVID-19 era

Abstract: Purpose Since the beginning of COVID-19 pandemic, social distancing and home confinement had a significant impact on children, especially on those with eating disorders (ED). The primary objective of this retrospective study was to describe and analyze the demographic and clinical profiles of children presenting with ED during the COVID-19 pandemic. Methods We conducted a retrospective review of clinical charts of patients with ED younger than 18 years who accessed the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…It is important to note that the COVID-19 pandemic and subsequent public health measures have resulted in a worsening of ED symptoms and an increase in psychological distress [ 24 ]. It is hard to measure the future impact of the pandemic on youth; however, data has consistently shown increased and worsening ED symptomatology since the onset of the pandemic which may represent greater incidence, prevalence, and/or acuity of EDs during the COVID-19 pandemic [ 25 , 26 , 27 ]. Finally, a recent study found a 60% increase of new onset AN or AAN diagnoses in youth compared to pre-pandemic rates, with the incidence of AN/AAN increasing from 24.5 to 40.6 cases per month [ 28 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…It is important to note that the COVID-19 pandemic and subsequent public health measures have resulted in a worsening of ED symptoms and an increase in psychological distress [ 24 ]. It is hard to measure the future impact of the pandemic on youth; however, data has consistently shown increased and worsening ED symptomatology since the onset of the pandemic which may represent greater incidence, prevalence, and/or acuity of EDs during the COVID-19 pandemic [ 25 , 26 , 27 ]. Finally, a recent study found a 60% increase of new onset AN or AAN diagnoses in youth compared to pre-pandemic rates, with the incidence of AN/AAN increasing from 24.5 to 40.6 cases per month [ 28 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…Our data showed this higher rate of pericardial involvement in patients with AN probably because, due to the COVID19 pandemic, patients with AN presented a more severe clinical status [25]. Conversely, none of our patients reported cardiac tamponade, which is considered a very rare complication in this group of patients in the literature [32].…”
Section: Discussionmentioning
confidence: 45%
“…In this setting, the increased number of young people requiring admission to health-care services because of ED has been linked to the onset of a real "ED epidemic" within the COVID-19 pandemic [23,24]. In particular, recent studies showed a more acute and severe ED onset during COVID-19 pandemic than in the recent past as well as an increased rate of psychiatric comorbidities and use of psychotropic drugs and a higher proportion of hospitalization [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Well documented research has proven that patients with eating disorders, especially with anorexia nervosa, are at risk of many somatic and psychiatric comorbidities and higher mortality ( 15 , 27 30 ). Our study results show a positive correlation between restrictive eating behavior and symptoms of depression.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the COVID pandemic has caused an increase in mental stress in children, adolescents, and their families worldwide. A rise in depression and anxiety disorders has been reported, as reflected by increased admissions due to severe eating disorders and suicide attempts ( 5 , 12 15 ).…”
Section: Introductionmentioning
confidence: 99%